A new live load model for bridges carrying light rail transit. (1st September 2018) - Kim, Yail J.; Ji, Yongcheng
Highlights: A new live load model for bridges carrying light rail transit loading is developed. Parametric investigations characterize light rail train loadings. The applicability of the standard load model is evaluated using 33 light rail trains. Abstract: This paper presents the development of a standard live load model for light rail bridges. It is recognized that the absence of a standard load model causes design outcomes varying from agency to agency, which is problematic from performance and reliability standpoints. A blend of deterministic and probabilistic approaches is employed to propose a new load model. Pursuant to light rail transit guidelines, benchmark bridges are designed (steel plate, prestressed concrete multicell box, reinforced concrete tee-beam, prestressed concrete I and bulb-tee, and steel box girder bridges). Finite element analysis is conducted to examine the response of the bridges when loaded by representative light rail trains operated in the United States (Colorado, Massachusetts, Minnesota, and Utah). Parametric investigations in conjunction with numerous loading configurations (48, 256 model cases) characterize light rail train loadings, and corresponding results are exploited to determine the extreme bending moments and shear forces of the bridges at four probability levels (the average, upper 20%, 99.9%, and 75-year categories). The upper 20% model shows load effects similar to the standard live load model (HL-93) of the American Association of State Highway and Transportation Officials (AASHTO) Load and Resistance Factor Design (LRFD) Bridge Design Specifications (BDS). The 99.9% and 75-year models envelop the moments and shear forces resulting from the representative light rail trains. These candidate load models are further assessed against site-based load inference. The 75-year model is selected and proposed to be the standard live load model entitled LRT-16 (a uniformly distributed load of 14 kN/m plus three axles of 150 kN at a spacing of 4.3 m, which is configured similarly to those of HL-93 in AASHTO LRFD BDS). The applicability of the standard load model is evaluated using 33 light rail tra.